The mechanism for solar irradiation enhanced evaporation and electricity generation. (October 2022) - Fang, Sunmiao; Chu, Weicun; Tan, Jin; Guo, Wanlin
Abstract: Generating electricity via natural water evaporation from porous materials is a promising energy-harvesting strategy and solar irradiation is a feasible and sustainable way to accelerate water evaporation. However, it is hard to enhance the evaporation-induced electricity by solar irradiation due to the lack of understanding on the working mechanism. Here we demonstrate that a tilted structure design with cheap carbon black materials can achieve about 180% enhancement in water-evaporation-induced power generation at a high-efficiency evaporation rate of up to 3.94 kg m -2 h -1 under one sun illumination. The enhanced water evaporation from the porous structure can continuously generate a voltage of up to 1.39 V with a maximum power density of about 0.103 mW m -2 without active electrodes involved. Detailed experimental results reveal that solar irradiation and thermal energy in the environment play a synergistic role in enhancing the output performance mainly through the electrokinetic effect of streaming potential. The facile structure design, easy-to-access materials and tilt angle dependent enhancement in evaporation and output performance in this work open a viable way to simultaneously harvest solar and environmental energy for cogeneration of freshwater and electric power. Graphical Abstract: ga1 Highlights: A tilted structure is designed for simultaneous vapor and power generation. Solar and environmental energy synergistically enhance water evaporation. A solar evaporation rate of 3.94 kg m -2 h -1 is achieved. Water evaporation continuously generates electric power.